2004
DOI: 10.1191/0269215504cr704oa
|View full text |Cite
|
Sign up to set email alerts
|

Eficacy of vestibular rehabilitation on chronic unilateral vestibular dysfunction

Abstract: There was a fast recovery in the supervised exercise session, whereas there was no significant difference in the home exercise session. These findings suggest that either supervised exercise is better than home exercise or that 10 supervised sessions are sufficient to get the end result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 12 publications
2
44
1
5
Order By: Relevance
“…Various exercise programs (home or supervised) have been described, including physical training, Cawthorne-Cooksey interventions, alternative strategies -such as Tai Chi -simulator-based training with virtual reality, etc. [3][4][5][6][7][8][9]. However, these vestibular rehabilitation strategies are not successful in patients with isolated otolith disorders [10].…”
Section: Introductionmentioning
confidence: 99%
“…Various exercise programs (home or supervised) have been described, including physical training, Cawthorne-Cooksey interventions, alternative strategies -such as Tai Chi -simulator-based training with virtual reality, etc. [3][4][5][6][7][8][9]. However, these vestibular rehabilitation strategies are not successful in patients with isolated otolith disorders [10].…”
Section: Introductionmentioning
confidence: 99%
“…After the title and abstract screening, 28 studies were identified as potentially eligible. However, after full text screening, 19 studies were excluded due to the following reasons: sample outside the pre-specified age range (n=14) [8][9][10][11][12][13][14][15][16][17][18][19][20][21] , lack of randomization (n=4) [22][23][24][25] , and sample with no complaints or vestibular disorders (n=1) 26 . Thus, nine randomized controlled trials were eligible for inclusion in this review and had their content critically analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Возраст и пол не влияют на степень вестибулярной компенсации, однако у пожилых она может занимать не-сколько большее время [22].…”
unclassified